(untitled) - Weaver, Samuel C. (Mason, OH., 2008)
Successful financial management begins with a solid understanding of the organization's strategic goals and objectives as well as its day-to-day business practices. Based in sound financial theory and journal literature augmented by common business policies, STRATEGIC FINANCIAL MANAGEMENT: APPLICATIONS OF CORPORATE FINANCE gives you the essential tools, techniques, and concepts you need in order to understand financial management from a strategic and operational perspective.
Keywords: Corporations,Doanh nghiệp; Finance,Tài chính